Omushkego materials, Maureen Matthews Papers - Bird, Louis; Carpenter, James; Hunter, Toby; Kataquapit, Joseph; Kataquapit, Michael; Koostachin, John George; Matthews, Maureen Anne, 1949-; Patrick, Michael; Tekakwitha, Catherine, Sister; Wesley, James (1976)
Audio recordings of interviews and narrations primarily by or with Louis Bird of Peawanuck. Major topics include Omushkegowak folklore, history, wihtigo, and other topics. The recordings include consist of three general types: stories and commentaries recorded directly by Louis Bird in Cree with some English explanation; interviews conducted by Louis Bird in Cree with elders and other residents of Peawanuck, Attawapiskat, and Kashechewan; and interviews by Maureen Matthews with Louis Bird in English on a variety of topics. Some of the interviews conducted by Matthews were recorded in the context of producing radio documentaries for CBC Radio One. (See Series I, Subseries 12 for the broadcast version of these documentaries.)